Kingmakers and\or Factionalists? Framing of ZANU PF Youths in The Herald and NewsDay. - Ndawana, Tonderai (Midlands State University, 2020)
This research seeks to find out how The Herald and NewsDay frame ZANU PF youths in the context of their daily reportage and news content, however some scholars who previously studied this interrelated area like Terence Ranger (2005) asserts that in postindependence Zimbabwe there is now what we call patriotic journalism basing on Zimbabwean print media reportage both in the private and public media sector. The researcher will also look at how The Herald and NewsDay have played a major role in adding pressure on the ZANU PF government through framing of the youths. In this study however, the researcher will also look at how Mugabe survive on power for a long period of time depending on the effect of youths as a strong party organ.The party youths coming up with, ZANU PF Youth Interface Rallies in a way to strengthen the party and by inviting Mugabe as way to preserve his position. ZANU PF party is also currently making use of repackaging of history as Terence Ranger (2005) argues, and its use and distortion of legitimate grievances contributed to patriotic blackness whereby Mugabe is touring countrywide on youth interface rallies forwarding his ideology. ZANU PF is currently maintaining its grip on youths to push its mandate, this can be reviewed by the One Million March which was attended by thousands of Zimbabweans marching through the capital Harare in support of President Robert Mugabe, but their number fell short of the ruling party's goal of attracting a million people. Demonstrators mostly youths attended the event from all over Zimbabwe for the march, organized by the Zanu-PF's youth wing in 2016.